2008
DOI: 10.1002/ajmg.a.32114
|View full text |Cite
|
Sign up to set email alerts
|

A new autosomal recessive syndrome of ocular colobomas, ichthyosis, brain malformations and endocrine abnormalities in an inbred Emirati family

Abstract: We report on an inbred Emirati family of Baluchi origin with ocular colobomas, ichthyosis, and endocrine abnormalities associated with midline brain malformations and mental retardation. All affected children had ocular colobomas, developmental delay and midline brain malformations. Hypoplastic pituitary gland was present in all three investigated children. Ichthyosiform dermatitis appeared in infancy in all surviving children. Other variable features include congenital heart defects, hypertrichosis and dark s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…4 In the family reported here, no clear abnormal transferrin mobility had been detected in two independent routine tests for CDG screening. Interestingly, in the family reported by Al-Gazali et al, 5 now also known to carry an SRD5A3 mutation, 3 repeated CDG testing had failed to detect any Total number of novel SNVs detected a 13 Total number of novel indels detected a 22…”
Section: Discussionmentioning
confidence: 99%
“…4 In the family reported here, no clear abnormal transferrin mobility had been detected in two independent routine tests for CDG screening. Interestingly, in the family reported by Al-Gazali et al, 5 now also known to carry an SRD5A3 mutation, 3 repeated CDG testing had failed to detect any Total number of novel SNVs detected a 13 Total number of novel indels detected a 22…”
Section: Discussionmentioning
confidence: 99%
“…It affects protein N-glycosylation, as well as the synthesis of mannose-linked glycans, C-mannosylation, and glycophospholipid anchor synthesis. SRD5A3-CDG is characterized by neurological and ophthalmological findings such as nystagmus, visual impairment, microphthalmia, cataract, coloboma (iris, chorioretinal), optic disk hypoplasia, and optic nerve hypoplasia/atrophy (Assmann et al 2001;Prietsch et al 2002;Al-Gazali et al 2008;Kahrizi et al 2009Kahrizi et al , 2011Morava et al 2009Morava et al , 2010Cantagrel et al 2010;Gr€ undahl et al 2012;Kara et al 2014;Kasapkara et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, Al-Gazali et al [110] reported on a consanguineous Emirati family of Baluchi origin with ocular colobomas, ichthyosis, and mental retardation associated with endocrine abnormalities and midline brain malformations. Six additional families with the same phenotype have later been identified [111] .…”
Section: Congenital Disorder Of Glycosylation Type1qmentioning
confidence: 99%